Performance Of Palm Shell Activated Carbon As An Alternative Adsorbent For Reclamation Of Used Transformer Oil - Ab Ghani, Sharin; Zainuddin, Hidayat; Muhamad, Nor Asiah (Asian Research Publishing Network (ARPN), 2015)
The objective of this study is to investigate the effectiveness of three types of adsorbents,namely Fuller’s earth,bentonite and palm shell activated carbon, on the reclamation of used transformer oil samples.Fuller’s earth is an industrial bleaching earth that is commonly used as an adsorbent in the reclamation process,whereas bentonite and palm shell activated carbon are alternative adsorbents that are relatively new in the field.In this study,the reclamation process is carried out on the used transformer oil samples five times,and the effectiveness of the adsorbents after the first,third and fifth reclamation cycle is examined.The relative content of dissolved decay products (DDP) for each sample before and after the reclamation process is determined using UV-Vis spectroscopy.In addition,the breakdown voltage test is performed to measure the dielectric strength of each sample under an applied electric field in accordance with the ASTM D6802 and MS IEC 60156:2012 standards.The reclamation process conducted in this study complies with the BS EN 60422:2013 and IEEE Std 637-1985 (R2007) standards.The results show that both bentonite and palm shell activated carbon adsorbents reduce the relative content of DDP by twice the value achieved by Fuller’s earth,particularly during the first and third reclamation cycles,while simultaneously enhancing the dielectric strength of the reclaimed oil samples.The results also show that the use of palm shell activated carbon gives the highest percentage of enhancement in the breakdown voltage test,with a value of 57.14% after the fifth reclamation cycle.Based on the results of this study,it can be concluded that palm shell activated carbon is a promising alternative adsorbent for reclamation of used transformer oils,which diversifies the uses of palm oil products in Malaysia.